Understanding Degenerative Cervical Myelopathy in Musculoskeletal Practice - Cervellini, Matteo; Feller, Daniel; Maselli, Filippo; Rossettini, Giacomo; Cook, Chad; Tabrah, Julia; Chauhan, Rohil V; Taylor, Alan; Kerry, Roger; Young, Ian; Dunning, James; Hutting, Nathan; et al. (Taylor and Francis Group, 2025)
BACKGROUND: Degenerative cervical myelopathy (DCM) is a clinical syndrome characterized by a progressive compression of the spinal cord. DCM often looks like common symptoms of aging or bilateral carpal tunnel syndrome in its early stages, requiring careful differential diagnosis. Identifying DCM is a real challenge as no validated screening tools are available for making the DCM diagnosis. Potentially, individuals with DCM may experience misdiagnosis or substantial diagnostic delays, with an enhanced risk of irreversible neurological consequences if not promptly addressed. Despite the increasing prevalence, there is a lack of awareness about DCM among both the public and healthcare professionals. However, patients may seek physiotherapy to obtain a diagnosis or access treatment. METHODS: A comprehensive (non-systematic) review of the literature about DCM epidemiology, pathophysiology, clinical presentation, diagnostic methods, and management was conducted. RESULTS: A guide and essential knowledge to facilitate clinicians to understand DCM and to enhance clinical reasoning skills, performance and interpretation of the examination are provided. Interdisciplinary collaboration and optimal referral methods are also handled. CONCLUSION: The aim of this article is to summarize and enhance physiotherapists' essential knowledge of the differential diagnosis and management of patients with DCM.
Keywords: guideline adherence; intervertebral disc degeneration; neck pain; Physiotherapy; Spinal cord diseases; spinal cord compression; 4201 Allied Health and Rehabilitation Science; 32 Biomedical and Clinical Sciences; 3202 Clinical Sciences; 42 Health Sciences; Minority Health; Neurosciences; Rare Diseases; Clinical Research; Health Disparities; 7.3 Management and decision making; 4.2 Evaluation of markers and technologies; Neurological; 1103 Clinical Sciences; 1106 Human Movement and Sports Sciences; Orthopedics; 3202 Clinical sciences; 4207 Sports science and exercise